Strategy To Improve The Potential Waqf Asset Management in Indonesia : Efficiency Approach - Ifa Hanifia Senjiati; Winwin Yadiati (Jurnal ASET (Akuntansi Riset), 2021)
waqf is the subject of discussion in the global issue. waqf is one of the instruments for economic recovery during a pandemic. The development of waqf is not accompanied good waqf management. The encountered problems are nadzir has insufficient knowledge an its causing inefficiency in managing waqf assets. Efficiency waqf institutions is measured by comparing targets and program planning and the data obtained are still descriptive.The urgency of this study is to analyze the efficiency of waqf management and how to develop its potential in the future. Thus, the qualitative method with Data Envelopment Analysis was used. The objects were five waqf institutions registered in the Indonesian Waqf Board and incorporated as a foundation in the 2014-2017 periods so that 20 financial reports were obtained. Input variables used were the operational costs and depreciation costs on assets under management, while the output variables were the revenue and the utilization of waqf funds. The contribution of this research is to provide solutions and steps that must be taken by nadzir waqf in Indonesia to improve the management of its waqf assets. The results are the consistently efficiency institutions reaching by Dompet Dhuafa Republika (2014-2017). The potential can get higher by reducing operational costs and depreciation assets. And then increasing the revenue and the utilization of waqf funds.